The Islamic moral economy : a study of Islamic money and financial instruments - Karim, Shafiel A. (Boca Raton, Fla. : Brown Walker Press, 2010)
Analyses the religious permissibility or lack thereof of the existing repertoire of financial instruments used in Islamic banking and finance. It also examines the utopian nature of the Islamic moral economy with a special emphasis in riba (financial interest and illogical increase), which is inescapable in the global economy, and therefore insoluble within the framework of the Islamic Moral Economy.
Includes bibliographical references (p. 109-133).
oif 08/09/14
Loan
Keywords: Banks and banking -- Islamic countries; Banking law (Islamic law); Finance -- Religious aspects -- Islam; Economics -- Religious aspects -- Islam